2008
DOI: 10.1677/erc-08-0098
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of hereditary medullary thyroid cancer: clinical implications for the surgeon, with a particular emphasis on the role of prophylactic thyroidectomy

Abstract: Medullary thyroid cancer (MTC) may occur either sporadically or on a hereditary basis. Hereditary MTC may be observed with either multiple endocrine neoplasia syndromes (MEN 2A and MEN 2B) or as familial MTC (FMTC). Despite the rarity of these syndromes, early diagnosis is especially important, since MTC is a lethal disease if not promptly and appropriately treated. Recently, the development of genetic testing and direct DNA analysis allows the identification of asymptomatic patients. Surgical prophylaxis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 113 publications
1
23
0
1
Order By: Relevance
“…A strong genetic component is known for medullary carcinoma, so that up to 25% of the cases are estimated to be heritable, caused by a gain-of-function germline mutation in the RET proto-oncogene (multiple endocrine neoplasia (MEN) type 2A and MEN2B and familial MTC (FMTC)) with an autosomal dominant mode of inheritance (Negri et al 2002, DeLellis et al 2004, Nose 2011. Despite the rarity of these syndromes and MTC in general, early diagnosis is especially important, since MTC is a lethal disease if not promptly and appropriately treated (Sakorafas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A strong genetic component is known for medullary carcinoma, so that up to 25% of the cases are estimated to be heritable, caused by a gain-of-function germline mutation in the RET proto-oncogene (multiple endocrine neoplasia (MEN) type 2A and MEN2B and familial MTC (FMTC)) with an autosomal dominant mode of inheritance (Negri et al 2002, DeLellis et al 2004, Nose 2011. Despite the rarity of these syndromes and MTC in general, early diagnosis is especially important, since MTC is a lethal disease if not promptly and appropriately treated (Sakorafas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in RET codons 630, 790, 791, 804 and 891 are capable of producing the MEN-2A phenotype [19]. Mutations at codon 634 (exon 11) occur in 85% of cases with C634R being the most frequent RET alteration in MEN-2A [20]. Mutations at exon 10 account for a further 10-15% of cases, whereas mutations at other exons are rare ( Fig.…”
Section: Men-2amentioning
confidence: 99%
“…When admitted, the majority patients have already progressed to MTC or exhibit lymph node metastasis. MTC is the predominant cause of death in patients with MEN2A (6), and it has previously been reported that 50% of patients are at risk of MTC recurrence (7). However, the appearance of MTC or MEN2A may differ among family members.…”
Section: Introductionmentioning
confidence: 99%